PENGGANTIAN SISTEM ABSENSI KARYAWAN PT. ABC DARI ID CARD MENJADI SISTEM DETEKSI WAJAH - Qomarotun Nurlaila (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2021)
The research was conducted to improve employee discipline in having absenteeis. PT. ABC has been using the attendance system with ID Card for 10 years. When employees forget to bring their ID cards, there will be a lot of manual work which is wasteful and can reduce employee productivity. In this study, an analysis of additional jobs was carried out because employees did not carry ID card.When the employee does not carry an ID card, the employee must write down the data in the book provided, the security officer must make sure the employee writes the data correctly, then delivers the book every morning to the HR payroll staff and takes it back every afternoon and the HR payroll staff must enter employee data manually to attendance data.Based on these conditions, the company, in this case the HR and IT department and in collaboration with all related departments, changed the attendance system from using an ID Card to a system with face detection.The face is a unique and inherent part of the body for every employee.The face is declared unique because everyone's face is different from one another even though they are twins.The application of the attendance system with face detection has an effect on improving employee discipline and productivity.